The Effect of Suggestopedia Method on Young Learners’ English Vocabulary Achievement at Destawan Hindu Orphanage - Desak Anugrah Dwi Kusuma (Universitas Pendidikan Ganesha, 2022)
English is a very important language to be taught and learnt because nowadays it is spoken by billions of people worldwide in many aspects of life. It makes people across the globe with English as L1, L2, and also foreign language need to learn English as well especially Indonesia. This study aimed to investigate the significant effects of the Suggestopedia method implementation on young learners’ vocabulary achievement. This study applied a quantitative method with a quasi-experimental design. The population of this study was children at the Destawan Hindu orphanage. The sample was 10 children classified as young learners (ages 7-12). Data were collected through a pretest-posttest which includes 20 MCTs. The experimental and control group data were analyzed using an independent samples t-test and Glass’s delta effect size. The finding revealed that the mean score of the experimental group was higher than the control group with a large Glass’s delta effect size (2.98 more than 0.80). In conclusion, the implementation of the suggestopedia method has a significant effect on young learners’ vocabulary achievement.